Comparison of neostigmine and sugammadex for hemodynamic parameters in neurointerventional anesthesia - Tsai, Yu-Hsun; Chen, Chun-Yu; Wong, Ho-Fai; Chou, An-Hsun (Frontiers in Neurology, 2023)
Background and purpose: Hemodynamic stability is important during neurointerventional procedures. However, ICP or blood pressure may increase due to endotracheal extubation. The aim of this study was to compare the hemodynamic effects of sugammadex and neostigmine with atropine in neurointerventional procedures during emergence from anesthesia. Results: Thirty-one patients were randomized to sugammadex, and thirty were randomized to neostigmine. Except for anesthesia time, there were no significant differences in any of the clinical characteristics between the two groups. The results demonstrated that the increase in MAP from period A to B was significantly greater in Group N than in Group S (regression coefficient = -10, 95% confidence interval = -17.3 to -2.7, P = 0.007). The MAP level was significantly increased from period A to B in the neostigmine group (95.1 vs. 102.4 mm Hg, P = 0.015), but it was not altered in Group S. In contrast, the change in HR from period A to B was not significantly different between groups. Conclusions: We suggest that sugammadex is a better option than neostigmine in interventional neuroradiological procedures due to the shorter extubation time and more stable hemodynamic change during emergence.